Silicon-phosphorus amorphous titanium dioxide-graphene oxide protective layer and its preparation method

CN122382685BActive Publication Date: 2026-09-01SHANDONG ACAD OF MARINE SCI (QINGDAO NAT MARINE SCI RES CENT)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610837582.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-11
Publication Date
2026-09-01
Estimated Expiration
2046-06-11

AI Technical Summary

Technical Problem

[0004]针对现有钛合金微弧氧化涂层因存在微孔、微裂纹等结构缺陷,在含氯离子环境中耐腐蚀性能不足,且现有封孔改性方法工艺复杂、成本高的问题,提供一种工艺简便、能显著提高涂层在含氯离子环境中抗腐蚀性能的钛合金表面复合涂层及其制备方法

Benefits of technology

[0022] Compared with existing technologies, this invention effectively improves the problem of easy penetration of corrosive media caused by defects such as micropores and microcracks in traditional oxide layers by constructing a TiO2/GO heterogeneous composite protective structure on the surface of the ceramic layer. In this invention, the formed TiO2 ceramic layer provides good hardness and basic protective performance; the introduced TiO2 nanoparticles further improve the film density; and the GO two-dimensional sheets can extend the Cl... - The diffusion paths of corrosive media such as H2O and O2 are blocked, thus forming a multi-layered synergistic barrier structure. Furthermore, the heterogeneous interface formed between the GO layers and TiO2 helps improve the overall stability of the composite layer, enhancing the structural integrity and corrosion resistance of the coating during long-term service. The preparation process of this invention is simple, the processing conditions are mild, and it does not require complex high-temperature and high-pressure equipment, making it easy to scale up. It can be applied to the surface protection of titanium alloys in aerospace, marine engineering, and chemical equipment fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122382685B_ABST
    Figure CN122382685B_ABST
Patent Text Reader

Abstract

This invention relates to the field of protective coating technology for titanium alloy surfaces, and particularly to a silicon-phosphorus amorphous phase titanium dioxide-graphene oxide protective layer and its preparation method. Specifically, a TiO2-based ceramic layer is constructed on the surface of TC4 titanium alloy, and graphene oxide and TiO2 nanoparticles are further used to form a composite closed structure, thereby improving the corrosion resistance, wear resistance and long-term service stability of the titanium alloy surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of protective coating technology for titanium alloy surfaces, specifically to a TiO2 / GO (graphene oxide) heterocomposite protective layer of TiO2 (titanium dioxide) nanoparticles and its preparation method. Background Technology

[0002] Titanium alloys are widely used in aerospace, marine engineering, and chemical equipment due to their high specific strength and excellent machinability. Titanium alloys themselves exhibit good corrosion resistance in atmospheric and oxidizing media because a dense TiO2 passivation film easily forms on their surface. However, in harsh environments containing high concentrations of chloride ions, these ions can locally damage the passivation film, leading to pitting corrosion, crevice corrosion, and other localized corrosion failures, severely limiting the long-term service life of titanium alloys in marine and high-humidity environments.

[0003] Micro-arc oxidation (MAO) technology can generate ceramic coatings in situ on the surface of titanium alloys to improve surface hardness and wear resistance. However, the inherent structural defects of traditional MAO coatings, such as volcanic micropores and microcracks, provide rapid penetration channels for corrosive media. Corrosive ions can easily penetrate the coating to reach the titanium alloy substrate, destroying the natural passivation film on the substrate surface and initiating corrosion of the substrate under the coating. This results in overall corrosion resistance lower than that of uncoated titanium alloys. Therefore, sealing the pores of the MAO coating to block the penetration path of corrosive media is crucial to improving the corrosion resistance of titanium alloys in chloride ion environments. Summary of the Invention

[0004] To address the issues of insufficient corrosion resistance in chloride-containing environments due to structural defects such as micropores and microcracks in existing titanium alloy micro-arc oxidation coatings, and the complexity and high cost of existing pore-sealing modification methods, this paper proposes a simple process for a titanium alloy surface composite coating that can significantly improve the corrosion resistance of the coating in chloride-containing environments, as well as its preparation method.

[0005] The present invention provides a silicon-phosphorus amorphous phase titanium dioxide-graphene oxide protective layer and its preparation method, in order to solve the problem that traditional ceramic protective layers have defects such as micropores and microcracks, which lead to easy penetration of corrosive media.

[0006] To achieve the above objectives, the present invention employs the following technical solution:

[0007] A method for preparing a silicon-phosphorus amorphous phase titanium dioxide-graphene oxide protective layer includes the following steps:

[0008] (1) Matrix pretreatment

[0009] The TC4 titanium alloy was machined into 15mm×15mm×5mm samples, and then polished sequentially with 240#, 400#, 800#, 1200# and 2000# silicon carbide sandpaper to remove scratches from the sample surface. Subsequently, the samples were ultrasonically cleaned in anhydrous ethanol for 10-15 minutes to completely remove and wash away the titanium alloy powder and silicon carbide sandpaper particles generated during the polishing process, while also cleaning away grease and organic contaminants from the sample surface. After cleaning, the samples were placed in a constant temperature drying oven at 60-80℃ for 30-60 minutes for later use.

[0010] (2) Preparation of ceramic layer

[0011] The electrolyte was prepared by adding Na3PO4·12H2O and Na2SiO3·9H2O to deionized water.

[0012] An electrochemical oxidation device was used, with the cleaned sample as the anode and a stainless steel tank as the cathode, to perform surface oxidation treatment under pulsed electrical parameters, resulting in a ceramic layer sample.

[0013] During the process, a ceramic layer structure with TiO2 as the main component is formed on the substrate surface. At the same time, the silicon and phosphorus components in the electrolyte participate in the film formation and form amorphous silicon-phosphorus oxides in local areas. This amorphous phase is like "glue" and can fill the micropores and microcracks in the coating, making the coating denser and thus blocking the penetration path of high concentrations of chloride ions in the ocean.

[0014] (3) Construction of TiO2 / GO heterogeneous composite sealing layer

[0015] The prepared ceramic layer sample was ultrasonically cleaned in anhydrous ethanol for 10–15 min.

[0016] A graphene oxide dispersion was prepared, and TiO2 nanoparticles were added. After stirring and ultrasonic dispersion, a uniform composite dispersion was formed, and the composite dispersion was then adjusted to be alkaline. The particle size of the TiO2 nanoparticles was 1–100 nm.

[0017] The specific method for preparing graphene oxide dispersion is as follows: weigh an appropriate amount of graphene oxide powder and add it to deionized water to prepare graphene oxide dispersion, and then use magnetic stirring and ultrasonic dispersion treatment.

[0018] The ceramic layer sample was immersed in a composite dispersion and dried at a constant temperature, allowing GO sheets and TiO2 nanoparticles to gradually deposit on the surface and pore areas of the ceramic layer. The two-dimensional GO sheets form a layered barrier structure, extending the diffusion path of the corrosive medium, while the TiO2 nanoparticles fill local defect areas and form a stable heterogeneous interface with the original ceramic layer, ultimately resulting in a TiO2 / GO heterogeneous composite protective layer.

[0019] The pulse electrical parameters of the electrochemical oxidation device are: positive voltage 430V, negative voltage 40V, operating frequency 800Hz, positive duty cycle 20%, and negative duty cycle 30%. Surface oxidation treatment is performed for 20 minutes under these parameters.

[0020] The present invention also provides a silicon-phosphorus amorphous phase titanium dioxide-graphene oxide protective layer, which is prepared by the above-described preparation method.

[0021] The beneficial effects of this invention are:

[0022] Compared with existing technologies, this invention effectively improves the problem of easy penetration of corrosive media caused by defects such as micropores and microcracks in traditional oxide layers by constructing a TiO2 / GO heterogeneous composite protective structure on the surface of the ceramic layer. In this invention, the formed TiO2 ceramic layer provides good hardness and basic protective performance; the introduced TiO2 nanoparticles further improve the film density; and the GO two-dimensional sheets can extend the Cl... - The diffusion paths of corrosive media such as H2O and O2 are blocked, thus forming a multi-layered synergistic barrier structure. Furthermore, the heterogeneous interface formed between the GO layers and TiO2 helps improve the overall stability of the composite layer, enhancing the structural integrity and corrosion resistance of the coating during long-term service. The preparation process of this invention is simple, the processing conditions are mild, and it does not require complex high-temperature and high-pressure equipment, making it easy to scale up. It can be applied to the surface protection of titanium alloys in aerospace, marine engineering, and chemical equipment fields. Attached Figure Description

[0023] Figure 1 This is a surface morphology diagram of the ceramic layer after oxidation and electrolysis treatment in Example 1.

[0024] Figure 2 This is a surface morphology diagram of the TiO2 / GO composite layer obtained in Example 2.

[0025] Figure 3 This is a comparison of the XRD phase diagrams of the ceramic layer and the composite layer.

[0026] Figure 4 This is a high-resolution XPS spectrum of carbon in the composite layer.

[0027] Figure 5 This is a high-resolution XPS spectrum of oxygen in the composite layer.

[0028] Figure 6 This is a comparison chart of the corrosion resistance performance of the ceramic layer and the composite layer, tested by electrochemical impedance spectroscopy (EIS).

[0029] Figure 7 This is a comparison chart of impedance moduli obtained from electrochemical impedance spectroscopy tests on ceramic and composite layers.

[0030] Figure 8 This is a phase angle comparison diagram of electrochemical impedance spectroscopy tests on the ceramic layer and the composite layer. Detailed Implementation

[0031] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of the embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.

[0032] This invention relates to a TiO2 / GO heterogeneous composite protective layer and its preparation method. Specifically, a TiO2-based ceramic layer is constructed on the surface of TC4 titanium alloy, and graphene oxide (GO) and TiO2 nanoparticles are further used to form a composite closed structure, thereby improving the corrosion resistance, wear resistance and long-term service stability of the titanium alloy surface.

[0033] Example 1: Preparation of the ceramic layer

[0034] This embodiment provides a method for preparing a ceramic layer on the surface of TC4 titanium alloy.

[0035] First, the TC4 titanium alloy was machined into a 15mm×15mm×5mm sample using wire cutting. Suspension holes were reserved on the edge of the sample for connecting the anode power supply during the subsequent oxidation process.

[0036] Subsequently, the sample surface was successively polished using 240#, 400#, 800#, 1200#, and 2000# silicon carbide wet sandpaper. During the polishing process, each grade of sandpaper was used to grind in the same direction. After the scratches caused by the previous grade of sandpaper had completely disappeared, a higher grit sandpaper was used to continue polishing to ensure that the sample surface was flat and uniform and to reduce local stress concentration areas.

[0037] After mechanical polishing, the sample is ultrasonically cleaned in anhydrous ethanol at a frequency controlled within the range of 40–80 kHz for 10–15 minutes to remove residual abrasive debris, oil, and other impurities from the sample surface. The sample is then thoroughly rinsed with deionized water and dried in a constant temperature drying oven at 60–80℃ for 30–60 minutes before use.

[0038] The electrolyte for oxidation treatment was prepared using a phosphate-silicate system. The specific steps were as follows: Na3PO4·12H2O and Na2SiO3·9H2O were weighed and added to deionized water, followed by continuous stirring using a magnetic stirrer to ensure complete dissolution of the electrolyte, ultimately yielding a homogeneous and transparent electrolyte system. The phosphate component improves the conductivity of the electrolyte and promotes the participation of phosphorus-containing components in the film formation process; the silicate component facilitates the entry of silicon into the ceramic layer, thereby improving the film stability and corrosion resistance.

[0039] Subsequently, surface treatment was performed using an electrochemical oxidation device, with a stainless steel tank as the cathode and the pretreated TC4 titanium alloy sample as the anode. The oxidation process parameters were set as follows: positive voltage 430V, negative voltage 40V, operating frequency 800Hz, positive duty cycle 20%, negative duty cycle 30%, and processing time 20 min.

[0040] During the oxidation process, the electrolyte temperature is controlled within the range of 20 to 40°C by a circulating cooling system to avoid problems such as unstable discharge, film ablation, and local structural abnormalities caused by excessively high electrolyte temperature.

[0041] Under high-energy discharge, instantaneous high-temperature micro-regions are formed on the surface of the titanium alloy, and melting, oxidation, and rapid solidification reactions occur on the substrate surface, thereby forming a TiO2-based ceramic layer with porous structure on the titanium alloy surface. Due to the high local temperature of the discharge channel, the molten oxides solidify rapidly during the cooling process, so the surface of the resulting ceramic layer exhibits typical porous structure characteristics.

[0042] The resulting ceramic layer mainly consists of anatase and rutile TiO2 phases. Simultaneously, silicon and phosphorus ions from the electrolyte participate in the film formation process, partially existing in the ceramic layer as amorphous silicon-phosphorus oxides. This amorphous silicon-phosphorus phase can fill local pores and crack defects to a certain extent, improving the overall structural stability of the coating. After oxidation treatment, the sample is removed from the electrolyte and thoroughly rinsed with deionized water to remove residual electrolyte, then allowed to air dry, thus obtaining a ceramic layer with a porous surface structure.

[0043] like Figure 1 As shown, the surface of the obtained ceramic layer contains numerous pores and localized cracks. Some discharge channels are relatively large, and obvious traces of melting and solidification can be observed at the edges of the pores. This is due to the rapid cooling and solidification of locally molten oxides during the discharge process. While numerous pores and cracks are beneficial for the subsequent deposition of sealing materials, they also create conditions for Cl... - Corrosive media can provide penetration channels, thus affecting the long-term stability of the protective layer.

[0044] The phase composition of the obtained ceramic layer was analyzed using X-ray diffraction (XRD), and the results are as follows: Figure 3 As shown in the figure. The results indicate that the obtained ceramic layer is mainly composed of anatase and rutile TiO2 phases, and α-Ti diffraction peaks originating from the TC4 matrix were detected. The anatase TiO2 phase mainly originates from oxides formed in relatively low-temperature regions, while the rutile phase mainly forms in locally higher-temperature regions.

[0045] The corrosion resistance of the ceramic layer was tested using an electrochemical workstation with a 3.5 wt.% NaCl solution as the test medium. A three-electrode system was employed, with a saturated calomel electrode as the reference electrode, a platinum sheet as the auxiliary electrode, and the sample as the working electrode. Figure 6 As shown, the Nyquist curve of the ceramic layer exhibits certain capacitive arc characteristics, indicating that the oxide layer can hinder the charge transfer process to a certain extent and improve the corrosion resistance of the titanium alloy. However, due to the presence of numerous pores and cracks in the film, corrosive media can still penetrate into the substrate through these defect areas. Figure 7 and Figure 8 As shown, the low-frequency impedance of the ceramic layer is relatively limited and the peak phase angle is low, indicating that its long-term barrier performance is still somewhat insufficient.

[0046] Example 2: Preparation of TiO2 / GO heterogeneous composite protective layer

[0047] This embodiment provides a method for preparing a TiO2 / GO heterogeneous composite protective layer, which is based on the ceramic layer prepared in Example 1, and further subjected to composite sealing treatment to improve the overall density and corrosion resistance of the coating.

[0048] First, the ceramic layer sample prepared in Example 1 was placed in anhydrous ethanol for ultrasonic cleaning for 15 minutes to remove loose particles and residual electrolyte adhering to the surface, and then air-dried for later use.

[0049] Subsequently, a GO / TiO2 composite dispersion was prepared. The specific steps were as follows: an appropriate amount of graphene oxide powder was weighed and added to deionized water to prepare a GO dispersion. Then, magnetic stirring and ultrasonic dispersion were used to improve the dispersion uniformity of the GO sheets in the aqueous solution.

[0050] Because GO contains a large number of oxygen-containing functional groups such as carboxyl, hydroxyl, and epoxy groups on its surface, it has good hydrophilicity in aqueous solutions.

[0051] Subsequently, TiO2 nanoparticles were added to the GO dispersion and ultrasonic dispersion was continued to ensure that the TiO2 nanoparticles were uniformly dispersed between the GO layers, thereby forming a stable GO / TiO2 composite dispersion system. The TiO2 nanoparticles, with a particle size of 1–100 nm, can effectively penetrate the pores and crack regions in the ceramic layer, thus improving the overall density of the composite layer.

[0052] The pH of the dispersion was then adjusted to the alkaline range using an alkaline solution. Under alkaline conditions, the oxygen-containing functional groups on the surface of the GO sheets ionize, resulting in a higher negative charge on the GO sheet surface. This improves its stable dispersibility in aqueous solution and enhances its adsorption with the ceramic layer. Simultaneously, the alkaline environment facilitates the formation of a more uniform and stable deposition structure of the GO two-dimensional sheets on the ceramic layer surface.

[0053] The cleaned ceramic layer sample was completely immersed in the aforementioned GO / TiO2 composite dispersion, ensuring the sample surface was fully covered by the liquid. The container holding the sample was then placed under constant temperature for drying. During the heating and drying process, as moisture gradually evaporated, GO two-dimensional sheets and TiO2 nanoparticles gradually deposited on the surface and within the pores of the ceramic layer. The GO two-dimensional sheets formed a layered barrier structure, extending the Cl... - The diffusion paths of corrosive media such as H2O and O2 are blocked; TiO2 nanoparticles can further fill local pores and crack defects, thereby improving the overall density and interfacial stability of the composite layer. Simultaneously, a stable heterogeneous interface structure can be formed between the GO sheets and TiO2 nanoparticles, further improving the stability and long-term service performance of the composite protective layer. After treatment, the sample is removed and allowed to cool naturally, thus obtaining the TiO2 / GO heterogeneous composite protective layer.

[0054] like Figure 2 As shown, compared to the ceramic layer in Example 1, the TiO2 / GO composite layer exhibits a significantly reduced number of pores on its surface. The original pores are partially covered by GO sheets and TiO2 nanoparticles, resulting in a more uniform and dense surface. The two-dimensional GO sheets form a layered stacked structure on the surface, while the TiO2 nanoparticles are dispersed between the GO sheets and in localized porous areas, thus forming a synergistic closed structure. Figure 1 Compared to the ceramic layer, the composite layer shows a significant reduction in continuous through-type defects, indicating that GO and TiO2 nanoparticles can effectively improve surface compactness.

[0055] like Figure 3 As shown, comparing the ceramic layer and the TiO2 / GO composite layer reveals that the composite layer, while retaining the original TiO2 crystal phase structure, exhibits a new diffraction peak near 2θ = 11.2°. This peak corresponds to the characteristic diffraction peak of the graphene oxide crystal plane, indicating that graphene oxide has been successfully deposited on the surface of the ceramic layer. Simultaneously, due to the GO sheets covering the surface, they exert a certain shielding effect on the diffraction signal of the underlying TiO2 crystal phase, thus reducing the intensity of some TiO2 diffraction peaks.

[0056] Figure 4This is a high-resolution XPS spectrum of carbon in the ceramic layer and TiO2 / GO composite layer during X-ray photoelectron spectroscopy (XPS). As shown in the figure, characteristic peaks such as CC, CO, C=O, and O=CO appear in the high-resolution C1s spectrum of the TiO2 / GO composite layer. Among them, the CO and C=O peaks have relatively high intensities, indicating that the graphene oxide retains a relatively abundant number of oxygen-containing functional groups. These oxygen-containing functional groups can not only improve the dispersion stability of GO in aqueous solution, but also enhance its interfacial bonding ability with the ceramic layer.

[0057] Figure 5 This is a high-resolution XPS spectrum of oxygen in the ceramic layer and TiO2 / GO composite layer during X-ray photoelectron spectroscopy (XPS) testing. As shown in the figure, the characteristic peak at 531.3 eV in the O1s high-resolution spectrum belongs to the Ti-O bond, the peak at 533.0 eV corresponds to the Si=O bond, and the peak at 535.6 eV belongs to the O=CO bond. The Ti-O bond originates from the TiO2 ceramic layer, while the O=CO bond originates from the carboxyl functional groups in graphene oxide. The simultaneous presence of Ti-O and O=CO bonds indicates that XPS simultaneously detects the chemical signals of the underlying ceramic layer and the surface GO layer, further proving that graphene oxide has been successfully composited onto the surface of the ceramic layer.

[0058] like Figure 6 , Figure 7 and Figure 8 As shown, electrochemical impedance spectroscopy was used to test the Nyquist plots, Modulus-frequency Bode plots, and Phase-frequency Bode plots of the ceramic layer and the TiO2 / GO composite layer, respectively. The results show that the TiO2 / GO composite layer has a larger Nyquist capacitive arc radius and a higher low-frequency impedance value, indicating superior corrosion resistance. This is because the synergistic barrier structure formed by the GO two-dimensional sheets and TiO2 nanoparticles effectively seals the pores and cracks in the ceramic layer, reducing the penetration rate of corrosive media into the matrix, thereby improving the long-term protective performance of the titanium alloy surface. Furthermore, the GO two-dimensional sheets have certain self-lubricating properties, which can reduce the shear stress at the friction interface, while the TiO2 ceramic layer provides high hardness support; therefore, the overall wear resistance of the composite layer is also improved.

[0059] The above description is merely an embodiment of this application and does not limit the patent scope of this application. Any equivalent structural or procedural transformations made using the content of this application's specification and drawings, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of this application.

Claims

1. A method for preparing a silicon-phosphorus amorphous phase titanium dioxide-graphene oxide protective layer, characterized in that, Includes the following steps: (1) Pretreatment of the matrix: The TC4 titanium alloy was processed into square thin sheet samples, and then polished step by step with silicon carbide sandpaper from coarse to fine. After that, it was ultrasonically cleaned in anhydrous ethanol and dried for later use. (2) Preparation of ceramic layer: Na3PO4·12H2O and Na2SiO3·9H2O were added to deionized water to prepare electrolyte; an electrochemical oxidation device was used, with the cleaned sample as the anode and the stainless steel tank as the cathode, and the surface oxidation was carried out under pulsed electrical parameters to obtain ceramic layer sample. The pulse electrical parameters of the electrochemical oxidation device are: positive voltage 430V, negative voltage 40V, operating frequency 800Hz, positive duty cycle 20%, and negative duty cycle 30%. Surface oxidation treatment is performed for 20 minutes under these parameters. (3) Construction of TiO2 / GO heterocomposite sealing layer: The prepared ceramic layer sample was ultrasonically cleaned in anhydrous ethanol. A graphene oxide dispersion was prepared and TiO2 nanoparticles were added. After stirring and ultrasonic dispersion, a uniform composite dispersion was formed. The composite dispersion was then adjusted to be alkaline. The specific method for preparing graphene oxide dispersion is as follows: weigh an appropriate amount of graphene oxide powder and add it to deionized water to prepare graphene oxide dispersion, and then use magnetic stirring and ultrasonic dispersion treatment. The ceramic layer sample was immersed in the composite dispersion and dried at a constant temperature to obtain the TiO2 / GO heterogeneous composite protective layer.

2. The preparation method according to claim 1, characterized in that, The square sheet sample has dimensions of 15mm × 15mm × 5mm.

3. The preparation method according to claim 1, characterized in that, The silicon carbide sandpaper has grit sizes of 240#, 400#, 800#, 1200# and 2000# respectively.

4. The preparation method according to claim 1, characterized in that, In the matrix pretreatment, the polished sample is ultrasonically cleaned in anhydrous ethanol for 10-15 minutes.

5. The preparation method according to claim 4, characterized in that, In the matrix pretreatment, the sample after being cleaned with anhydrous ethanol is placed in a constant temperature drying oven at 60-80℃ and dried for 30-60 minutes.

6. The preparation method according to claim 1, characterized in that, The TiO2 nanoparticles have a particle size of 1–100 nm.

7. A silicon-phosphorus amorphous phase titanium dioxide-graphene oxide protective layer, characterized in that, It is prepared by the preparation method according to any one of claims 1-6.

Citation Information

Patent Citations

  • Preparation method of wear-resistant titanium alloy micro-arc oxidation coating

    CN113151877A

  • High-temperature-corrosion-resistant stainless steel gas distribution disc and preparation method thereof

    CN120945456A